2018
DOI: 10.1016/j.molmed.2018.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Human Endogenous Retroviruses in Neurological Diseases

Abstract: The causes of multiple sclerosis and amyotrophic lateral sclerosis have long remained elusive. A new category of pathogenic components, normally dormant within human genomes, has been identified: human endogenous retroviruses (HERVs). These represent ∼8% of the human genome, and environmental factors have reproducibly been shown to trigger their expression. The resulting production of envelope (Env) proteins from HERV-W and HERV-K appears to engage pathophysiological pathways leading to the pathognomonic featu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
239
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 235 publications
(244 citation statements)
references
References 104 publications
3
239
0
2
Order By: Relevance
“…Human endogenous retroviruses (HERVs) are relics of the infective retrovirus integrated into the human genome, accounting for approximately 5%‐8% of the human genome, including at least 31 families . They participate in the regulation of various physiological and pathological activities in humans through different pathways . Most of the HERVs genes lose their transcriptional ability due to mutation or partial deletion, but some genes remain intact as open reading frames and can be translated into functional proteins, such as Syncytin 1.…”
Section: Introductionmentioning
confidence: 99%
“…Human endogenous retroviruses (HERVs) are relics of the infective retrovirus integrated into the human genome, accounting for approximately 5%‐8% of the human genome, including at least 31 families . They participate in the regulation of various physiological and pathological activities in humans through different pathways . Most of the HERVs genes lose their transcriptional ability due to mutation or partial deletion, but some genes remain intact as open reading frames and can be translated into functional proteins, such as Syncytin 1.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, an earlier study has reported that transposons are not an abundant source of enhancers in the mammalian neocortex (Emera et al , ). We speculate that keeping HERV sequences silent in brain may be of particular importance because of the several neurological diseases associated with HERV expression in that tissue, including multiple sclerosis, amyotrophic lateral sclerosis, and chronic inflammatory demyelinating polyradiculoneuropathy (Küry et al , ). We note also that the low usage of HERVs in pancreatic islets is yet another similarity between this tissue and brain tissues, which in numerous studies have been reported to share transcriptional programs (Arntfield & van der Kooy, ).…”
Section: Discussionmentioning
confidence: 99%
“…Retroviruses are associated with a broad spectrum of neurological disorders (3)(4)(5)(6)(7)(8)(9). HIV has been associated with an ALS-like motor neuron disease in over 30 patients (3)(4)(5)(6).…”
Section: Mechanismsmentioning
confidence: 99%
“…HERV expression is also increased in a number of other neurological (7,28,29) and non-neurological diseases, such as cancer (30). Furthermore, some think that HERVs may play beneficial roles in the pathophysiology of certain diseases (31); however, this may not be the case in all diseases as research on multiple sclerosis has suggested a pathogenic role for HERVs (32,33).…”
Section: Mechanismsmentioning
confidence: 99%